Performance Measurement and Effective Communication: Strategic to Service Delivery (British Journal of Multidisciplinary and Advanced Studies, 2023)
The Bomet County Government is experiencing difficulties in providing efficient services and should integrate performance contracting as a means of enhancing it. The objective was to establish the effect of performance measurement and effective communication, on service delivery. The study used the expectancy, goal-setting and new public management theories. Explanatory research design was used with a sample of 70 management staff selected out of a target population of 260. The research employed a semi-structured questionnaire to gather data, which was subsequently analysed using descriptive and inferential statistics. The findings indicated that performance measurement and effective communication had significant effect on service delivery.  Accountability resulted in the timely completion of projects and innovation improved project prioritization. The study suggested that enhancing communication strategies and reassessing performance evaluation methods could help enhance service delivery